Neighbourhood socio-economic disadvantage and loneliness: the contribution of green space quantity and quality - Tara Jamalishahni; Gavin Turrell; Sarah Foster; Melanie Davern; Karen Villanueva (BMC, 2023)
Abstract Disadvantaged areas experience higher levels of loneliness than advantaged areas, though studies rarely identify environmental determinants of neighbourhood inequity in loneliness. We studied the contribution of the quantity and quality of green space to neighbourhood inequity in loneliness in three buffer sizes (400 m, 800 m, 1600 m), using cross-sectional data from 3778 individuals aged 48-77 years old living in 200 neighbourhoods in Brisbane, Australia. Levels of loneliness were significantly higher in disadvantaged neighbourhoods, and these neighbourhoods had less green space and less access to quality green space. However, there was no evidence that neighbourhood disparities in green space contributed to the association between neighbourhood disadvantage and loneliness. Possible methodological and substantive reasons for this result are discussed.